2021
DOI: 10.5171/2021.907184
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Solutions to Overcome the Health Services Crisis within the Covid-19 Era

Abstract: The outbreak of the SARS-CoV-2 pandemic has fundamentally changed the natural course of activity of all economic sectors worldwide, as well as the healthcare sector which was deeply influenced. This paper analyzes the relationship between the increased demand for health services during the pandemic and the limited supply of healthcare using the transversal method for some European Union (EU) states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Further, given the wide application of AI in healthcare, the extent of literature on AI technology in the context of a resilient and sustainable healthcare system is minimal and under-researched (Dasgupta et al, 2022;van der Schaar et al, 2021;Milne-Ives et al, 2020). The recent literature has either only focused on the resilient healthcare system (Abdel-Basset et al, 2021;Sitharthan and Rajesh, 2021;Wang and Alexander, 2021;Leimanis and Palkova, 2021;Pascu-Gabara and Cepoi, 2021;Bansal et al, 2020) or the sustainable healthcare system Elavarasan et al, 2021;Rahman et al, 2021a;Mishra et al, 2021a;Ahmed et al, 2021;Hsu et al, 2021;Ahad et al, 2020;Yigitcanlar and Cugurullo, 2020). As a result, a combination of resilience and sustainability in the context of AI in healthcare is not yet discussed in any single work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, given the wide application of AI in healthcare, the extent of literature on AI technology in the context of a resilient and sustainable healthcare system is minimal and under-researched (Dasgupta et al, 2022;van der Schaar et al, 2021;Milne-Ives et al, 2020). The recent literature has either only focused on the resilient healthcare system (Abdel-Basset et al, 2021;Sitharthan and Rajesh, 2021;Wang and Alexander, 2021;Leimanis and Palkova, 2021;Pascu-Gabara and Cepoi, 2021;Bansal et al, 2020) or the sustainable healthcare system Elavarasan et al, 2021;Rahman et al, 2021a;Mishra et al, 2021a;Ahmed et al, 2021;Hsu et al, 2021;Ahad et al, 2020;Yigitcanlar and Cugurullo, 2020). As a result, a combination of resilience and sustainability in the context of AI in healthcare is not yet discussed in any single work.…”
Section: Introductionmentioning
confidence: 99%
“…The paper presents a multidimensional review of the factors that create significant technological, organizational, ethical, data, policy, political and legal challenges for AI adoption. Unlike the previous systematic reviews Wang and Alexander, 2021;Pascu-Gabara and Cepoi, 2021;Ahad et al, 2020;Haleem and Javaid, 2020;Angioni, and Musso 2020;Sonnessa et al, 2017), the authors use the extended antecedents, practices, and outcome themes to provide a novel research framework drawn from the systematic literature review. We also observed that past studies lack in proving future research directions using any framework (Elavarasan et al, 2021;Hsu et al, 2021;Wang and Wu, 2021;Islam et al, 2021;Haleem and Javaid, 2020;Berquedich et al, 2020).…”
Section: Introductionmentioning
confidence: 99%